А New Homo Economicus - is the Future Human Image: Methodological Research Tools - Oksana Petinova (International Society of Philosophy and Cosmology, 2014)
In this article the author focuses on the consideration of the features of the modeling method in the context of the methodology of the new economic man study. Attention is focused on the fact that the formation of the current global economic system is philosophical problematization of economic knowledge which contains search for new forms and methods of research and presentation not only in academic discourse, but also socially meaningful contexts. The author concludes that the subject area of the total review of the traditional model of economic man and designing new models in the framework of theoretical and empirical contexts involves interrelated economic, ideologi-cal, socio-cultural, psychological, spiritual, political, ethical segments that require philosophical comprehension. The economic motivation of human behavior in the system of market relations associated with existential axiological selection problems of care about the future of modern life with the problems of identifying opportunities, social values and ideals, a change for the better socio -economic life. We are talking about multifactor model that includes a wide range of features and integrated indicators of viability, but successfully replacing uncertain characteristics of a real object is completely defined by ideal projections. The viability of the model depends on its represen-tative capacity, combined with other models, completeness penetration of socially significant pro-gram of activities that define the norms of social and economic interaction between people, social and cultural continuity degree.